Analysis Of The Effect Of Cost Efficiency (BOPO) And Capital Adequacy Ratio (CAR) On Profitability (ROA): (Case Study: Bank Syariah Indonesia In The Makassar Area 2021-2025) - Muh Amrih (Yayasan Inovasi Kemajuan Intelektual, 2026)
This study aims to analyze the effect of cost efficiency, as proxied by Operating Costs to Operating Income (BOPO), and the Capital Adequacy Ratio (CAR), on profitability, as proxied by Return on Assets (ROA), at Bank Syariah Indonesia (BSI) in the Makassar region for the period 2021-2025. As the largest Islamic banking merger entity in Indonesia, BSI faces the challenge of operational integration and capital optimization in a competitive regional market such as Makassar. This study uses a quantitative approach employing panel data regression. The results partially indicate that BOPO has a significant negative effect on ROA, confirming that cost efficiency is key to profit sustainability. Meanwhile, CAR has a significant positive effect on ROA, indicating that strengthening the capital base provides banks with greater flexibility to channel productive financing. Simultaneously, these two variables strongly influence the bank's financial health. This study contributes to BSI management in formulating efficiency strategy policies at the regional branch level.